Mulheres e a multiplicidade de papéis: a retramatização das escolhas no momento atual - Souza, Sandra Aparecida de (2017)
There is currently a quest to find out who is the new woman that has emerged after all the social transformations and the inclusion of the new roles. By the same token, there is an effort to rescue the ancestral sense of being a woman. This essay presents a contribution to the Psychodrama in the use of the re-plotting technique. The qualitative research was applied with the sociodrama method and the use of re-plotting. The intention is to investigate and reflect on the choices women make today, considering the transformations and multiplicity of their roles in society. The research was done with a group of women, attracted by curiosity and also by the search for reflection on their social roles. The choice of re-plotting to investigate the woman's roles was appropriate because it sought the individual threads to later weave the plot of the collective stories. The bibliographic survey shows the secondary role that women have played throughout history and the transformations of their roles. The outcome of the intervention in the group demonstrated what choices these women make. In addition, it provoked reflections on the women about the individual and collective role that were evidenced at the end of the session